Spectrum of congenital anomalies among VACTERL cases: a EUROCAT population-based study - van de Putte, Romy (2020)
Background: The VACTERL (Vertebral anomalies, Anal atresia, Cardiac malformations, Tracheo-Esophageal fistula, Renal anomalies, Limb abnormalities) association is the non-random occurrence of at least three of these congenital anomalies: vertebral, anal, cardiac, tracheo-esophageal, renal, and limb anomalies. Diagnosing VACTERL patients is difficult, as many disorders have multiple features in common with VACTERL. The aims of this study were to clearly outline component features, describe the phenotypic spectrum among the largest group of VACTERL patients thus far reported, and to identify phenotypically similar subtypes. Methods: A case-only study was performed assessing data on 501 cases recorded with VACTERL in the JRC-EUROCAT (Joint Research Centre-European Surveillance of Congenital Anomalies) central database (birth years: 1980-2015). We differentiated between major and minor VACTERL features and anomalies outside the VACTERL spectrum to create a clear definition of VACTERL. Results: In total, 397 cases (79%) fulfilled our VACTERL diagnostic criteria. The most commonly observed major VACTERL features were anorectal malformations and esophageal atresia/tracheo-esophageal fistula (both occurring in 62% of VACTERL cases), followed by cardiac (57%), renal (51%), vertebral (33%), and limb anomalies (25%), in every possible combination. Three VACTERL subtypes were defined: STRICT-VACTERL, VACTERL-LIKE, and VACTERL-PLUS, based on severity and presence of additional congenital anomalies. Conclusion: The clearly defined VACTERL component features and the VACTERL subtypes introduced will improve both clinical practice and etiologic research.